Gastric polypoid lesions: Analysis of 150 endoscopic polypectomy specimens from 91 patients - (:unkn) unknown (W J G PRESS, 2003)
AIM: To analyze gastric polypoid lesions in our patient-population with respect to histopathologic features and demographic, clinical, and endoscopic characteristics of patients. METHODS: Clinical records and histopathologic reports of patients with gastric polypoid lesions were analyzed retrospectively. All lesions had been totally removed by either endoscopic polypectomy or hot biopsy forceps. The histopathologic slides were re-evaluated by the same histopathologist. RESULTS: One-hundred and fifty gastric polypoid lesions were identified in 91 patients. There were 53 (58%) women and 38 (42%) men with a median age of 53 (range, 31 to 82) years. The most frequent presenting symptom was dyspepsia that was observed in 35 (38.5%)patients. Symptoms were mostly related to various associated gastric abnormalities such as chronic gastritis or H pylori infection rather than polypoid lesion itself. Polypoid lesions were commonly located in the antrum followed by cardia. Out of 150 lesions, 80 (53%) had the largest dimensions less than or equal to 5 mm and only 7 were pedunculated. The frequencies of hyperplastic polyps, foveolar hyperplasia, and fundic gland polyps were 46%, 18%, and 14% respectively. We also detected gastritis varioliformis in 12 specimens, lymphoid follicles in 9, 4 adenomatous polyps in 4, polypoid lesions with edematous mucosa in 4, inflammatory polyps in 3, and carcinoid tumor in 1. Adenomatous changes were observed within two hyperplastic polyps and low grade dysplasia in one adenoma. Histopathologic evaluation of the surrounding gastric mucosa demonstrated chronic gastritis in 72 (79%) patients and H pylori infection in 45 (49%). CONCLUSION: Hyperplastic polyps are the most frequently encountered subtype of gastric polypoid lesions. They are usually associated with chronic gastritis or H pylori gastritis. Contrary to the previous belief, they may harbour adenomatous changes or dysplastic foci. Therefore, endoscopic polypectomy seems as a safe and fast procedure for both diagnosis and treatment of gastric polypoid lesions at the same session. In addition, edematous mucosa may appear misleadingly as a polypoid lesion in some instances and it can be ruled out only by histopathologic examination.
Keywords: HYPERPLASTIC POLYPS; MALIGNANT TRANSFORMATION; OUTLET OBSTRUCTION; SEX DISTRIBUTION; SURVEILLANCE; FREQUENCY; PATHOLOGY; LOCATION; STOMACH; RISK